Statistical methods used in medical research and cancer registries: A review - Nazir Ahmad Dar; Tavseef Ahmad Tali; Basharat Ahmad Gani; Mushtaq Ahmad Sofi; Shahid Rashid Sofi; Nazir Ahmad Khan; Arshad Manzoor Najmi; Afroz Fir; Syed Nisar Ahmad (Journal of Radiation and Cancer Research, 2023)
Medicine is an ever-changing science. Thus, new knowledge is generated by research and clinical experience. Statistical methods used in medical research play a vital role in medical research to draw a meaningful conclusion about research. Analyzing data and interpreting results is the most exciting stage of research, but it is not possible for everyone. It is possible for those who is having deep knowledge and to know the applicability of statistical methods used in medical research. Commonly used statistical methods in medical research are descriptive and inferential statistical methods. In descriptive statistical methods, we describe our data by the organization of our data in the form of tabulation and diagrams, measures of central tendency, dispersion, condensation, and measures of correlation. In inferential statistics, we draw a meaningful conclusion whether our treatment or procedure used in medical research gives a fruitful outcome or not. It is possible only when we have a good knowledge and skill of statistical methods used in basic research and it allows our clinical researchers to draw accurate and reasonable conclusions. Statistics provides us with sound methods in collecting data about observing health-related events, which in turn helps us in summarizing and analyzing the results so as to draw valid inferences regarding the hypothesis of our research. During the research, scientists used different statistical methods such as independent t-test or Student's t-test and Chi-square test to compare the different treatments used in the experimental studies to check whether there was a significant difference in our treatment or not. The main role of a cancer registry is to capturing a clear and complete picture of the cancer burden. To show how confident the researchers are that the results did not happen by chance, they use confidence intervals. For example, 95% confidence means that the researchers are pretty sure that the result has not happened by chance. The motive and aim of my review article are only to aware the researchers to know the importance and applicability of these statistical methods used in medical research and cancer registries.